The ionization efficiency of aluminum and iron at meteoric velocities. (July 2018) - DeLuca, Michael; Munsat, Tobin; Thomas, Evan; Sternovsky, Zoltan
Abstract: The ionization efficiency of aluminum was measured in the laboratory over an extended velocity range of 10.8–73.4 km/s and compared to available models. The measurements were made by shooting submicron-sized aluminum dust particles into an air chamber using the University of Colorado's dust accelerator facility. The ionization efficiency, β, is calculated from the total charge generated in the chamber during the complete ablation of particles of known mass. An array of photomultiplier tubes observed the light production by a subset of particles in the chamber to confirm that a moderate deceleration of the ablating particles occurred at low velocities. This information allows the interpretation of the β measurements to be extended to velocities <20 km/s, with the understanding that the low-velocity β measurements are lower limits. Updated β measurements for iron particles are also reported over an extended velocity range compared to previously published data: 10.5–87.3 km/s. The measurements are fit to functions for the ionization efficiency across the entire velocity range, and a semi-empirical function is presented which matches the shape of the measured β curves for aluminum and iron at both high and low velocities. Highlights: The ionization efficiency of aluminum was measured using a dust accelerator. Slowdown was observed by tracking the light production of the particles. Updated ionization efficiency measurements for iron are presented. The measurements are fit to functional forms for the ionization efficiency.